2016
DOI: 10.1007/978-3-319-39406-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Effects of Cell Death in Malignant Disease

Abstract: Although apoptosis is well recognized as a cell death program with clear anticancer roles, accumulating evidence linking apoptosis with tissue repair and regeneration indicates that its relationship with malignant disease is more complex than previously thought. Here we review how the responses of neighboring cells in the microenvironment of apoptotic tumor cells may contribute to the cell birth/cell death disequilibrium that provides the basis for cancerous tissue emergence and growth. We describe the bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 185 publications
1
68
0
Order By: Relevance
“…Less intuitively, aggressive, rapidly growing tumors also display high AIs. Indeed, close association between high AI and high proliferative rate has been reported for multiple aggressive cancers, including colorectal carcinoma, bladder, lung and breast cancers, leukemia, and lymphoma ( 6 ). To place these observations in perspective, it has long been known that in Burkitt’s lymphoma, for example, which displays evidence of both high mitotic and apoptotic indices in standard histological sections, a substantial proportion (around 70%) of the proliferating cells die ( 7 ).…”
Section: Introduction: Apoptosis and Oncogenesismentioning
confidence: 88%
“…Less intuitively, aggressive, rapidly growing tumors also display high AIs. Indeed, close association between high AI and high proliferative rate has been reported for multiple aggressive cancers, including colorectal carcinoma, bladder, lung and breast cancers, leukemia, and lymphoma ( 6 ). To place these observations in perspective, it has long been known that in Burkitt’s lymphoma, for example, which displays evidence of both high mitotic and apoptotic indices in standard histological sections, a substantial proportion (around 70%) of the proliferating cells die ( 7 ).…”
Section: Introduction: Apoptosis and Oncogenesismentioning
confidence: 88%
“…of a number of the pro-oncogenic properties of TAMs (19,35,36,77,78). TAMs acquire a phenotype favoring proliferation, angiogenesis, tissue invasion and metastasis, and evasion of immune destruction (19,35,36,71,72,77,78). TAMs are also intimately involved in remodeling of the extracellular matrix and in creating an environment more conducive to tumor growth (19,35,36).…”
Section: Apoptotic Cells Induce Selective Epithelial Cell Adaptationmentioning
confidence: 99%
“…A striking complexity characterizes the flow of information from apoptotic cells to live cells (1)(2)(3)(4)19). Information can be extracted from multiple death-related variables, including the mode of cell death (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of this process, cancer cells can release EVs that may subvert cells of the immune system within the tumour microenvironment [12]. Christopher Gregory (MRC Centre for Inflammation Research, The University of Edinburgh, UK) described how apoptotic cells in the tumour microenvironment can activate endothelial cells (which in turn promote angiogenesis) and macrophages, both of which then support the tumour in what Prof Gregory terms the 'onco-regenerative niche' [18]. Elke Pogge von Strandmann (University of Cologne, Germany) showed that by activating the retinoic acid-inducible gene I in malignant B cells EVs were released with the ability to trigger natural killer cells to kill the tumour cells [19].…”
Section: Tumour Extracellular Vesicles and The Immune Systemmentioning
confidence: 99%